Public and private sector zero-deforestation commitments and their impacts: A case study from South Sumatra Province, Indonesia - Purnomo, H.; Okarda, B.; Puspitaloka, D.; Ristiana, N.; Sanjaya, M.; Komarudin, H.; Dermawan, A.; Andrianto, A.; Kusumadewi, S.D.; Brady, M.A. (Elsevier, 2023)
In Asia, Africa, and Latin America, complex drivers of deforestation have sparked mandatory and voluntary initiatives, including moratorium policies, zero-deforestation pledges and certification systems. The impacts of these different commitments, which aim to reduce deforestation, have yet to be documented or analytically scrutinized. Using South Sumatra as a case study, we used the Institutional Analysis and Development (IAD) framework to identify the context and impacts of public and private sector commitments. Public sector commitment was assessed by examining political will reflected in government policies and regulations, while private sector commitment was assessed by looking at compliance with mandatory and voluntary certification schemes. South Sumatra lost 63% of its natural forest between 1990 and 2019. Deforestation is driven by expansion of large-scale commercial plantations, as well as illegal logging and clearing. Our study indicates that public and private sector commitments do matter. Statistically, we found sufficient evidence that private sector commitments were able to significantly reduce deforestation from year of commitments to 2019, at a 90% confidence level. Efforts to support zero-deforestation commitments must involve radical shifts in current policy and practice, with stricter law enforcement to combat illegal activities, greater transparency to inform progress, and the development of strategic and actionable plans.